Experimental Determination of the Phonon-Eigenvectors of Silicon Carbide by Raman Spectroscopy - Hundhausen, Martin; Ley, Lothar; et al. (Materials Science Forum, 2002)
The phonon frequencies of silicon carbide (SiC) depend on the atomic masses of the constituent elements Si and C. In general, the frequency decreases, when the mass of one kind of atom is increased by isotopic substitution. Quantitatively, the shift of a phonon line in the Raman spectrum due to such a substitution depends on the phonon eigenvector of the isotopically modified constituent atom. We measure the frequency shifts for Raman active modes in SiC polytypes, when the 12C-isotope is replaced by 13C and calculate the absolute value of the eigenvector of the carbon sublattice from these results. With these results a validation and improvement of the force constants used in a linear-chain model to calculate phonon dispersion curves is possible. © 2002 Trans Tech Publications.
UnivIS-Import:2015-04-14:Pub.2002.nat.dphy.IAP.LAP.experi_5
Keywords: Phonon dispersion curves; Phonon eigenvectors; Raman spectroscopy